The Effect Of Warm Water Therapy On Reducing Spinal Pain In Pregnant Women At Antang Health Center In Makassar City - Ani T Prianti; Nurul Fitri Sugiarti Syam (Lembaga Pengembangan Kinerja Dosen, 2023)
Spinal pain in pregnancy is caused by hormonal, musculoskeletal, and stressful changes. Spinal pain in pregnancy if left untreated will have an impact on the quality of life and daily activities of pregnant women The management of spinal pain in pregnancy can include pharmacological and non-pharmacological. Non-pharmacological pain management is warm water therapy. Warm water therapy provides the effect of rirelaxation, vasodilation of blood vessels, removes metabolic waste that is no longer in use, and reduces muscle spasmsThe purpose of this study is to determine the effect of warm water therapy on reducing spinal pain in pregnant women at the Antang Health Center, Makassar City in 2022 This research is a quantitative study with a quasi-experimental design non-equivalent with one group pre-test post-test. The total population of 64 respondents with a sample of 30 respondents who met the inclusion criteria, the independent variable was warm water therapy and the dependent variable was the reduction of spinal pain in pregnant women. The results of the spinal pain scale study before warm water therapy were carried out on a moderate pain scale (4-6) there were 15 respondents with a percentage (50%). And after a warm compress was carried out, there were 18 respondents with a percentage (60%). The result of p value is 0.000 (<0.05), so Ha is accepted. There is an effect of providing warm water therapy on reducing spinal pain in pregnant women at the Rsu at the Antang Health Center, Makassar City in 2022The conclusion of this study is the effect of warm water therapy on reducing bone pain in pregnant women at the Antang Health Center, Makassar City in 2022. It is hoped that there will be further research on other non-pharmacological techniques against spinal pain in pregnancy.